The Impact of "2D / 3D" Simulations in Developing Students' Skills of Computer Maintenance at Albaha University - العديل، عبدالله خليفة (جامعة أم القرى, 2021)
The study focuses on the impact of (2D/ 3D) dimensions simulations in developing some computer maintenance skills for students at College of Education, AlBaha University. A quasi-experimental method used for purpose of this study. To achieve the aim of the study, it was implemented achievement test and observation checklist with 60 learners. The researcher used a t-test to measure the difference between the first experimental (taught by 2D simulation) and second experimental (taught using 3D simulation) groups. Results indicates a significant difference between the mean students’ scores of the first and second experimental groups in post achievement-test in favor of second group in computer maintenance skills. In addition, there was a significant difference found in observation checklist in post-test in favor of second group in computer maintenance skills. Consequences of this study specified efficiency of 3D simulation in developing some computer maintenance skills for students.
تركز الدراسة على أثر المحاكاة ثنائية وثلاثية الأبعاد في تنمية بعض مهارات صيانة الحاسب لطلاب كلية التربية، جامعة الباحة. وقد تم استخدام التصميم شبه التجريبي لغرض هذه الدراسة. ولتحقيق هدف الدراسة، تم تنفيذ اختبار تحصيلي وبطاقة ملاحظة مع 60 طالباً. استخدم الباحث اختبار "ت" لقياس الفرق بين المجموعة التجريبية الأولى (تدرس بالمحاكاة ثنائية الأبعاد) والمجموعة التجريبية الثانية (تدرس باستخدام المحاكاة ثلاثية الأبعاد)، وتشير النتائج إلى وجود فرقاً جوهرياً بين متوسط درجات الطلاب للمجموعة التجريبية الأولى والثانية في الاختبار التحصيلي البعدي لصالح المجموعة الثانية في مهارات صيانة الكمبيوتر، بالإضافة إلى ذلك، كان هناك اختلافاً جوهرياً في بطاقة الملاحظة في الاختبار البعدي لصالح المجموعة التجريبية الثانية في مهارات صيانة الحاسب الآلي. حددت نتائج هذه الدراسة كفاءة المحاكاة ثلاثية الأبعاد في تنمية بعض مهارات صيانة الكمبيوتر لدى الطلاب.
Keywords: المهارات الحاسوبية -- المحاكاة ثلاثية الأبعاد -- طلبة الجامعات -- الجامعات السعودية